PREDICTION OF WELL BEHAVIOR USING WELL DELIVERABILITY ANALYSIS - Dewi Asmorowati; M. Waziz Wildan; Khasani - (ASEAN Journal of Systems Engineering, 2014)
In operating geothermal field, the thing to note is the sustainable production as well as problems that affect it. The problem that often occurs in the geothermal field is scale, corrosion and mechanical problems. One technique that can be used to predict the problems that occur around the bottom hole to the surface is using the well deliverability analysis method. Analysis is done by data and curve interpretation of deliverability curve based on Grant experiment. This study take data from several wells in two Geothermal Field in Indonesia. From the analysis, well A, D and F show production decline The deliverability curve of well A shows the production decline for about 60 – 85%, it is caused by moving of the flashing point, it shows from the increasing of dryness value from 7-14% in 1997 become 13-15% in 2010. The deliverability curve of well D shows the production decline for about 50%, it is caused by declining of reservoir pressure that can be seen from the decreasing  of feed zone pressure in 1997 is 27 bar and in 2010 is 20 bar. The deliverability curve of well F shows the production decline for about 29%, it is caused by moving  of the flashing point.